The function of justification in transnational governance - Poul F. Kjaer (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2015)
Developing a sociological informed social theory perspective, this article asks the question why social praxis' of justification has moved to the centre-stage within the debate on transnational ordering. In contrast to perspectives which see the relationship between national and transnational forms or ordering as characterised by a zero-sum game, the coevolutionary and mutually reinforcing relationship between national and transnational forms of ordering is emphasised. It is, moreover, argued that this complementarity can be traced back to the fundamentally different function and position of national and transnational forms of ordering in world society. The widespread attempt to analyse transnational developments on the basis of concepts of law and the political which emerged in national contexts are therefore seen as problematic. Instead context adequate concepts of transnational law and politics are needed. It is on this background, that a discourse on justification has emerged in relation to transnational settings. Transnational justificatory praxis' can be understood as functional equivalents to democracy in transnational settings in so far as both can be understood as reflexivity increasing instruments. The central difference is, however, that democratic frameworks implies an ex ante form of the political in contrast to the ex post emphasis of justificatory praxis'. In addition, law gains a central role as the framework through which justificatory praxis' are structured in transnational settings. This discussion paper is part of a series of contributions to the conference "Towards a Grammar of Justice in EU Law', which took place on 6-7 November 2014 at VU University Amsterdam, sponsored by ACCESS EUROPE Amsterdam, VU Centre for European Legal Studies and the Dutch Research Council VENI grant.
Keywords: 320; justification; transnational law; transnational politics; global governance; democracy